Technological and Methodological Advances in Plastic Recycling: A Systematic Literature Review - Delgado Cartagena, Dayanna Aracelly; Treviño Zevallos, Italo Francisco (LACCEI, 2025)
The evolution of technologies and efficient methods in plastic recycling has transformed waste management, offering new opportunities to mitigate environmental pollution and promote the circular economy. This study analyzes 50 research papers that explore the latest advancements in this field. It highlights that methods such as mechanical, chemical, enzymatic, and advanced thermal recycling have a significant impact on sustainability and efficiency. Findings indicate that mechanical recycling, although widely used due to its low cost, has limitations regarding the quality of the recovered material. In contrast, chemical and advanced thermal recycling enable greater resource recovery by breaking down polymers into monomers or basic products, although they require higher energy investments. Innovations such as enzymatic recycling show great potential for processing complex plastics, opening new perspectives in the field. The results also emphasize the need to optimize processes and develop infrastructure to overcome challenges such as material purity and operational costs, ensuring a higher recovery rate. Additionally, the study underscores the importance of integrating these technologies with public policies and circular economy models to maximize their positive impact on the environment and reduce plastic pollution.